Skeletal cryptococcosis from 1977 to 2013 - Zhou, Heng-Xing; Lu, Lu; Chu, Tianci; Wang, Tianyi; Cao, Daigui; Li, Fuyuan; Ning, Guangzhi; Feng, Shiqing (Frontiers in Microbiology, 2015)
Skeletal cryptococcosis, an aspect of disseminated cryptococcal disease or isolated skeletal cryptococcal infection, is a rare but treatable disease. However, limited information is available regarding its clinical features, treatment, and prognosis. This systematic review examined all cases published between April 1977 and May 2013 with regard to the factors associated with this disease, including patient sex, age, and epidemiological history; affected sites; clinical symptoms; underlying diseases; laboratory tests; radiological manifestations; and delays in diagnosis, treatment, follow-up assessments, and outcomes. We found that immune abnormality is a risk factor but does not predict mortality; these observations are due to recent Cryptococcus neoformans var gattii (CNVG) outbreaks. Dissemination was irrespective of immune status and required combination therapy, and dissemination carried a worse prognosis. Therefore, a database of skeletal cryptococcosis cases should be created.